2009
DOI: 10.1155/2009/356120
|View full text |Cite
|
Sign up to set email alerts
|

A General Rate K/N Convolutional Decoder Based on Neural Networks with Stopping Criterion

Abstract: A novel algorithm for decoding a general rate K/N convolutional code based on recurrent neural network (RNN) is described and analysed. The algorithm is introduced by outlining the mathematical models of the encoder and decoder. A number of strategies for optimising the iterative decoding process are proposed, and a simulator was also designed in order to compare the Bit Error Rate (BER) performance of the RNN decoder with the conventional decoder that is based on Viterbi Algorithm (VA). The simulation results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The methods for soft decoding of convolutional codes based on the search in the code trellis and the application of neural networks [15][16][17][18][19] can be used only for convolutional codes with a small code constraint length (V ≤ 9) due to the rapid growth of computational complexity. According to the research results, the presented method ensures decoding of the convolutional code with a quite large code constraint length (V ≤ 16).…”
Section: Discussion Of Results Of Analyzing Efficiency Of the Bioinspmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for soft decoding of convolutional codes based on the search in the code trellis and the application of neural networks [15][16][17][18][19] can be used only for convolutional codes with a small code constraint length (V ≤ 9) due to the rapid growth of computational complexity. According to the research results, the presented method ensures decoding of the convolutional code with a quite large code constraint length (V ≤ 16).…”
Section: Discussion Of Results Of Analyzing Efficiency Of the Bioinspmentioning
confidence: 99%
“…In paper [18], the method for decoding the convolutional codes with an arbitrary encoding rate based on recurrent neural networks was proposed and encoding optimization strategies were given. The research conducted in the work showed that this decoding method provides reliability of information transmission at the level of the Viterbi method, but with a lower computational complexity and the possibility of parallel information processing.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Different ideas around the use of ANNs for decoding emerged in the 1990s with works such as [16]- [18] for decoding block and hamming codes. Subsequently, ANNs were used for decoding convolutional codes in [19], [20]. In [21], the author used MLPs to generate Low-Density Parity-Check (LDPC) codes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the deployment of Artificial Neural Networks (ANN), to train the system for higher fault tolerance in OFDM is used by Praveenkumar [8]. There are also other works [9][10][11] based on AI trying to solve problems related to coding theory.…”
Section: Introductionmentioning
confidence: 99%